2005
DOI: 10.1155/mi.2005.221
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Therapy on Rats Submitted to Subtotal Nephrectomy: Role of Antioxidant System

Abstract: Chronic renal failure (CRF) represents a world health problem. Ozone increases the endogenous antioxidant defense system, preserving the cell redox state. The aim of this study is to evaluate the effect of ozone/oxygen mixture in the renal function, morphology, and biochemical parameters, in an experimental model of CRF (subtotal nephrectomy). Ozone/oxygen mixture was applied daily, by rectal insufflation (0.5 mg/kg) for 15 sessions after the nephrectomy. Renal function was evaluated, as well as different bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 31 publications
2
33
0
4
Order By: Relevance
“…Apart from the major enzymatic antioxidants, such as superoxide dismutase, GSH peroxidase, and catalase, estrogens are also classified as nonenzymatic antioxidants that delay or inhibit age-associated pathological and biological changes. [57] Several experimental studies have shown that antioxidant capacity of tissues is decreased in animals with CRF, [58,59] while marked reductions in plasma glutathione concentration and glutathione peroxidase activity, as well as marked increases in the ratios of oxidized to reduced GSH were observed in CRF patients. [60,61] Current findings show that the reduction in GSH content of the studied tissues of male and ovariectomized rats may be due to its consumption during CRF-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the major enzymatic antioxidants, such as superoxide dismutase, GSH peroxidase, and catalase, estrogens are also classified as nonenzymatic antioxidants that delay or inhibit age-associated pathological and biological changes. [57] Several experimental studies have shown that antioxidant capacity of tissues is decreased in animals with CRF, [58,59] while marked reductions in plasma glutathione concentration and glutathione peroxidase activity, as well as marked increases in the ratios of oxidized to reduced GSH were observed in CRF patients. [60,61] Current findings show that the reduction in GSH content of the studied tissues of male and ovariectomized rats may be due to its consumption during CRF-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were described by (Martínez et al, 2001) who report a significant increase in the activity of SOD in animals treated with ozone therapy. In addition (Calunga et al, 2005) also report a significant increase in the enzymes of the antioxidant defense system in animals treated with ozone therapy. The increase in the antioxidant enzyme activities along with the decrease in the levels of the oxidant biomarkers MDA and THP is evidence of the protecting effect of the cosmetic formulation for oxidative stress in the skin.…”
Section: Resultsmentioning
confidence: 84%
“…The increase in the antioxidant enzyme activities along with the decrease in the levels of the oxidant biomarkers MDA and THP is evidence of the protecting effect of the cosmetic formulation for oxidative stress in the skin. Other authors (Calunga, 2005; report a significant decrease in the oxidant biomarkers and an improvement in the antioxidant defence system in groups of animals treated with ozone gas before experimental subtotal nephrectomy or endotoxic shock. The unexpected behavior of conjugated dienes could be due to the transitory character of these compounds since they are intermediate products of lipid peroxidation and in the presence of oxygen, react very rapidly to form lipoperoxidic radicals.…”
Section: Resultsmentioning
confidence: 92%
“…De esta manera podemos ver el efecto inmunoregulador de la ozonoterapia, el cual contribuye a la disminución del proceso inflamatorio en nuestra patología 31 y a la mejoría de la función pulmonar. además, la ozonoterapia posee un poderoso efecto estimulador de las defensas antioxidantes 13,[16][17][18][19][20][21] , que impide la progresión del proceso destructivo del tejido pulmonar.…”
Section: Discussionunclassified
“…a nivel preclínico se ha observado una modulación a nivel de tejido pulmonar lesionado de la enzima mieloperoxidasa. Todos estos aspectos hacen pensar que la aplicación del ozono en pacientes con EPOc, podría tener un efecto beneficioso [13][14][15][16][17][18][19][20][21] .…”
unclassified